Case study - M-commerce at Helsana Health Insurance: Mobile premium calculator - Reichold, A; Schierholz, R; Kolbe, L; Brenner, W; SOCIETY, IC; SOCIETY, IC; SOCIETY, IC (2003)
The advancement of Information and Telecommunication Technologies allows new types of interaction between companies and customers. Companies face the question which potentials can be exploited using new communication and transaction channels and which challenges must be overcome in doing so. The design of the interaction between customer and company is of crucial importance. Depending on the process requirements different alternatives of communication can be chosen.The following case study describes a project and the implemented solution integrating a mobile channel into the acquisition process of a health insurance provider. It gives insight into a way of using mobile channels and what aspects a company needs to take into account when implementing solutions using mobile technology.